Environmental Estrogens and Breast cancer - llmiawati llmiawati (Faculty of Medicine, Universitas Andalas, 2014)
Background: Recent studies revealed that various man-made chemicals disrupting properties with endocrine- contribute in the development of breast cancer.objective: To review the state of the science of the endocrine-disrupting chemicals (EDC) and their role in the development of breast cancer.Methods: Key papers on experimental and epidemiologic studies examining the associations between EDC and breast cancer were searched throJgh the Google Sch-olar and pubMedusing Results: EDC effects depend on the level and timing of exposure, with critical window on developmentalstages. Diethylstilbestrol(DES) and bispIenolA(BpA) aretwo thoroughlystudied environmental estrogenic compounds. Epidemiological studies showed increased breast cancer incident in women exposed to DES during gestation. ExperimentalstuQies revealed that BPA induces architectural and gene expression froRte changes ir i